Kewirausahaan : manajemen usaha kecil - Justin G. Longenecker (Salemba Empat, 2001)
ast jil.1 =c.1-5 jil.2 =c.1-4/tr, jil.2=c.5-7, jil.1=c.6 (jl.lengkap ISBN:979-691-042-8); (Jl.1 ISBN: 979-691-043-8)